CONVENTIONAL MEDIA OF COMMUNICATION BROADCAST INTEGRATION AND THE INTERNET TO PRIVATE BROADCAST RADIO - Harliantara Harliantara; Daniel Susilo (Commed : Jurnal Komunikasi dan Media, 2018)
Radio broadcasting is the oldest electronic media. It is nearly a century of its existence and tries to keep the existence of overcoming tough competition by the presence of other media. In general, the motivation to exist is influenced by survival factors broadcasters themselves. Recently, it emerged new technologies and methods of distribution that has a profound effect on the way in which the audience listening to radio through the Internet. In the process of radio communications, conventional radio broadcasters have added internet media. The study recommends the meaning communication process in media integration on conventional radio and the internet as a media convergence. This study used qualitative approach that still has not been done to the study of conventional media of communication broadcast integration and the internet to private broadcast radio with the data collection conducted through field observations, interviews, and documentation. In this study, the researcher selected resource persons who were aware of the radio broadcasting situation. The determinations of informants were interviewed by purposively, which chosen by consideration and specific purposes. Data were analyzed using qualitative data analysis. The data obtained from various sources, using data collection techniques (triangulation), and it carried out continuously until the data saturated. The researcher also analyzed the data with the process of arranging data order, organized them with the interpretation, provided a significant meaning to the analysis, as well as an explaining description to the pattern of dimensions. The process was carried out with data analysis techniques to perform three (3) aspects in a systematic analysis of data reduction, data display, and conclusion. This study confirms that the meaning of the communication process of conventional media of communication broadcast integration and the internet as media convergence to become crucial in improving the knowledge of radio broadcasting at the present and in the future. Besides that, the study found that the current radio broadcasting, in addition to broadcast in the form of sound or noise, it also broadcasts in live streaming or podcasts streamed over the Internet (network) in the form of voice, text, images and video.